دور الإدارة المحلية في التنمية البيئية بلدية المسيلة انموذجا - عبد الكبير احمد (جامعة المسيلة, 2019)
لقد قامت هذه الدراسة على إبراز دور الإدارة المحلية في التنمية البيئية في الجزائر، في ظل الترسانة القانونية المتعلقة بالبيئة، حيث تمحورت إشكالية الدراسة حول كيفية مساهمة الإدارة المحلية في تنمية البيئة . وتمّ إجراء دراسة ميدانية لبلدية المسيلة والتوصّل إلى الإجابة على الفرضية الأولى المتمثلة في حماية العناصر البيئية والمحافظة على التوازن الطبيعي لها، حيث يكون باستخدام الوسائل والإمكانيات المتوفّرة لاستغلال أمثل للثروات وتجنب ضررها، أمّا الفرضية الثّانية فتمّ التوصّل إلى أنّ قوانين الإدارة المحلية غير كافية لتنمية البيئة نتيجة لضعف المنتخب المحليّ وعدم كفاءته وفعاليته في مجال البيئة والمشاركة في سَنّ القوانين، مع تقديم توصيات في أعادة النظر في قوانين البلدية في مجال البيئة وكذا المنتخبين ، إضافة إلى تسخير الوسائل الماديّة والبشرية للقضاء على المشاكل البيئيّة لإحداث التنمية والحصول على بيئة نظيفة وسليمة. الكلمات المفتاحية : الإدارة المحلية – البيئة – التنمية البيئية – المشكلات البيئية – المجتمع المحلي This study hidhlighted the role of local administration in the development of Algeria in light of the legal arsenal related to the environment. The problem of the study focused on how the local administration contributes to the Development of the environment.A fieled study was conducted in town of M’sila and reaching to the answer the first hypothesis which protect environmental elements and maintaining its natural balance where it is using the means and possibilities available and the optimal exploitation of wealth and avoid harm. The second hypothesis was that the local administration laws are insufficient to develop the weakness of the local team, its inefficiency and effectiveness in the field of the environment and participation in enacting laws, with recommendation in revision of municipal laws in the field of environment as well as elected .In addition to harness the physical and human means to eliminate environmental problems for development events and get a clean and healthy environment key words : Local administration - Environment - Environmental development - Environmental problems - Local community
Keywords: الإدارة المحلية – البيئة – التنمية البيئية – المشكلات البيئية – المجتمع المحلي